2005
DOI: 10.1063/1.1882769
|View full text |Cite
|
Sign up to set email alerts
|

Influence of composition on relaxor ferroelectric and electromechanical properties of poly(vinylidene fluoride-trifluoroethylene- chlorofluoroethylene)

Abstract: We investigate the influence of the composition, especially the chlorofluoroethylene content, on the ferroelectric and electromechanical properties of the poly(vinylidene fluoride-trifluoroethylene- chlorofluoroethylene) (PVDF-TrFE-CFE). It was found that increasing the CFE from 0to9mol% gradually converts the normal ferroelectric of the copolymer (in the compositions range of VDF/TrFE mole ratio between 64∕36 to 75∕25) to a relaxor ferroelectric, resulting in a nearly hysteresis free polarization loop and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 13 publications
4
50
0
Order By: Relevance
“…At high CFE mol% (>8.5 mol%) in the compositions range of VDF/TrFE mole ratio between 64/36 to 75/25, the polar phase region is no longer detectable, indicating a complete conversion to the relaxor ferroelectric phase and the terpolymer exhibits the highest strain level with very little hysteresis. They compared the measured strain as a function of the applied field for two compositions of 65/35/8.6 mol% and 75/25/5.3 mol% 10 . The presence of the polar-phase in the terpolymer of 75/25/5.3 mol% greatly reduces the electrostrictive strain in the polymer.…”
Section: Terpolymer P(vdf-trfe-cfe)mentioning
confidence: 99%
See 1 more Smart Citation
“…At high CFE mol% (>8.5 mol%) in the compositions range of VDF/TrFE mole ratio between 64/36 to 75/25, the polar phase region is no longer detectable, indicating a complete conversion to the relaxor ferroelectric phase and the terpolymer exhibits the highest strain level with very little hysteresis. They compared the measured strain as a function of the applied field for two compositions of 65/35/8.6 mol% and 75/25/5.3 mol% 10 . The presence of the polar-phase in the terpolymer of 75/25/5.3 mol% greatly reduces the electrostrictive strain in the polymer.…”
Section: Terpolymer P(vdf-trfe-cfe)mentioning
confidence: 99%
“…The presence of the polar-phase in the terpolymer of 75/25/5.3 mol% greatly reduces the electrostrictive strain in the polymer. On the other hand, increasing CFE content causes reduction in crystallinity, which will affect the elastic modulus and the induced polarization level of the polymer 10 . There competing effects determine the desired terpolymer compositions for given application.…”
Section: Terpolymer P(vdf-trfe-cfe)mentioning
confidence: 99%
“…A change in electro-physical properties of the copolymer can be achieved not only by varying the molar VDF and TrFe ratios and by using the proper electro-mechanical and heat treatments, but also by introducing defects by high energy electron [6][7][8] and gamma radiations [9] or adding the chemical monomer chlorofluoroethylene (CFE) [10]. It has been found that such treatments convert the normal ferroelectric copolymer to a relaxor one.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical properties of the P(VDF-TrFE) copolymer can be substantially changed not only as a result of electromechanical and thermal actions but also under electron [13][14][15][16] and gamma irradiation [17,18], as well as upon introduction of the chlorofluoroethylene monomer into the copolymer matrix [19]. It has been demonstrated that, upon this treatment, the copolymer transforms into a relaxor state [13,15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%